The Influence of Taxpayer Understanding, Information Technology, And Tax Audit Intensity on Perceptions of Tax Evasion - Widyana, Mellania Fitria; Widiyati, Dian (International Journal of Education, Information Technology, and Others, 2024)
The purpose of this research is to examine the impact of taxpayer understanding, information technology, and the frequency of tax audits on individuals’ perceptions regarding the morality of tax evasion. The study is based on a population of 142,629 individuals, with a sample size of 150 respondents chosen through convenience sampling as outlined by the Slovin formula, specifically focusing on taxpayers registered at KPP Pratama Pondok Aren. Data collection was conducted via questionnaires, and the analysis was performed using multiple linear regression with SPSS version 26. The findings indicate that the frequency of tax audits has a significant effect on the perception of tax evasion ethics, whereas taxpayer understanding and information technology do not exhibit any notable impact. This study enhances the understanding of taxpayer ethics and behavior, and recommends the use of more diverse research methods and the inclusion of additional variables for more in-depth results.